2023
DOI: 10.1002/brb3.2952
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy improves cognitive function in dementia: A systematic review and meta‐analysis

Abstract: This study aimed to investigate the effectiveness of phototherapy intervention on cognitive function in older adult patients with dementia. PubMed, Ovid MEDLINE, Web of Science, EMBASE, Cochrane Central Registry of Controlled Trials, PsycINFO, and Clinical Trials were searched from their inception to August 10, 2022, for randomized controlled trials involving patients with dementia who received phototherapy interventions. We used the weighted mean difference (MD) or standard weighted mean difference to generat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In a randomized controlled trial, artificial morning dawn simulation light exposure led to improvements in subjective well-being, mood, and cognitive performance compared with both dim light and bright monochromatic blue light (Gabel et al, 2013). Researchers have also investigated light as a therapeutic intervention for addressing sleep and circadian disruptions in PLWD (Lu et al, 2023; Mitolo et al, 2019). A systematic review explored the influence of light treatment on sleep, cognition, mood, and behavior in people with Alzheimer's, revealing mixed effects but highlighting the potential of light therapy with minimal adverse effects (Mitolo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a randomized controlled trial, artificial morning dawn simulation light exposure led to improvements in subjective well-being, mood, and cognitive performance compared with both dim light and bright monochromatic blue light (Gabel et al, 2013). Researchers have also investigated light as a therapeutic intervention for addressing sleep and circadian disruptions in PLWD (Lu et al, 2023; Mitolo et al, 2019). A systematic review explored the influence of light treatment on sleep, cognition, mood, and behavior in people with Alzheimer's, revealing mixed effects but highlighting the potential of light therapy with minimal adverse effects (Mitolo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another review showed a positive effect on cognitive function among PLWD, yet it did not yield significant effects on BPSD or sleep (Lu et al, 2023). The review suggested that there is a need for additional carefully planned studies to investigate the optimal clinical implementation conditions for light therapy, encompassing factors such as type of light (e.g., bright, blue, or blue–green light), device type (e.g., light box, ceiling mounted light, helmets, and glasses), duration, frequency, and timing (Lu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous studies, exposure to bright light may improve sleep and ease depression and agitation in people with AD ( Peter-Derex et al, 2015 ; van Maanen et al, 2016 ; Roccaro et al, 2020 ). Persons living with AD or vascular dementia who were exposed to bright light therapy (BLT) demonstrated significantly improved scores on the Mini-Mental State Examination (MMSE) scale, compared to exposure to dim light therapy ( Lu et al, 2023 ). BLT has also been used for decades to treat nonseasonal depression and other mood disorders ( Al-Karawi and Jubair, 2016 ; Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Roccaro et al [22] conducted a systematic review of research examining the effect of light therapy in alleviating sleep and rhythm disorders in patients with AD, concluding that light therapy ameliorates circadian rhythm disturbances and sleep efficiency (SE) in patients with AD. Furthermore, previous studies have indicated that light therapy can reduce cognitive decompensation and depression behavior in patients with AD [23,24], however, further research is warranted to add to the scarce evidence on its usefulness. Compared with prior meta-analyses, our meta-analysis had a relatively larger number of included articles and outcome metrics, expanded the sample size, and only included randomized controlled trials (RCTs) to reduce sampling error.…”
Section: Introductionmentioning
confidence: 99%